Dignity of informal caregivers of migrant patients in the last phase of life: a qualitative study - de Voogd, X. (BMC Palliat Care, 2021)
BACKGROUND: A key aim of palliative care is to improve the quality of life of patients and their families. To help ensure quality of life for the families of patients with migrant backgrounds, this study sought insights into the dignity of informal caregivers in migrant communities. This could improve understanding of family-centered care for migrant patients. METHODS: Twenty semi-structured interviews with informal caregivers of Turkish, Moroccan, or Surinamese background living in the Netherlands were analyzed thematically. RESULTS: The dignity of the patient and that of their informal caregivers were found to be strongly interrelated. Most important for the dignity of caregivers was ensuring good care for their patients and preserving the patients’ dignity. Ensuring good care involved advocating for good and dignified care and for satisfaction of a patient’s wishes. For many informal caregivers, it also included delivering care to the patient by themselves or together with other family members, despite having to give up part of their own lives. Providing care themselves was part of maintaining a good relationship with the patient; the care was to cater to the patient’s preferences and help preserve the patient’s dignity, and it could be accompanied by valuable aspects such as times for good conversations. Positive interaction between an informal caregiver and a patient positively influenced the informal caregiver’s dignity. Informal caregiver and patient dignity were often compromised simultaneously; when informal caregivers felt healthcare professionals were undermining a patient’s dignity, their own dignity suffered. According to informal caregivers, healthcare professionals can help them preserve dignity by taking seriously their advice about the patient, keeping them informed about the prognosis of the disease and of the patient, and dealing respectfully with differences in values at the end of life. CONCLUSION: The dignity of migrant patients’ informal caregivers in the last phase of a patient’s life is closely entwined with ensuring good care and dignity for the patient. Healthcare professionals can strengthen the dignity of informal caregivers by supporting their caregiving role. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12904-021-00721-6.